Fantastic metamorphoses, other worlds : ways of telling the self - Warner, Marina, 1946- (Clarendon lectures in English ;, 2004)
"Metamorphosis is a dynamic principle of creation, vital to natural processes of generation and evolution, growth and decay. In this book, Fantastic Metamorphoses, Other Worlds: Ways of Telling the Self, Marina Warner also explores how ideas of individual identity and consistency are threatened if a person is subject to a continual process of transformation. Shape-shifting belongs too in the landscape of magic, witchcraft, and wonder, in classical mythology, early modern fairy tales and the uncanny fiction of the last two centuries." "Mutating, Hatching, Splitting, Doubling - Marina Warner's exhilarating journey of exploration tracks the four dominant metamorphic processes to reveal their power in evoking personality. She covers a dazzling range of topics and suggests richly unexpected connections. All this is set against a background of historical encounters with other cultures, especially of the Caribbean, and presented with her characteristic zest." "Beginning with Ovid's great poem, Metamorphoses, a founding text of the metamorphic tradition, she carries us into the fantastic art of Hieronymus Bosch, the legends of the Taino people, the life cycle of the butterfly, the myth of Leda and the Swan, the genealogy of the Zombie, the pantomime of Aladdin, the haunting of doppelgangers, the coming of photography, and the late fiction of Lewis Carroll."--Jacket